Effect of metal loading on the CO2 methanation: A comparison between alumina supported Ni and Ru catalysts - Quindimil, Adrián; De-La-Torre, Unai; Pereda-Ayo, Beñat; Davó-Quiñonero, Arantxa; Bailón-García, Esther; Lozano-Castelló, Dolores; González-Marcos, José A.; Bueno-López, Agustín; González-Velasco, Juan R. (Catalysis today, 2020)
[Display omitted] •Increasing loading of Ni and Ru increases the surface basicity and forms new CO2 adsorption sites.•High calcination temperature leads to an increase of RuO2 particle size and formation of inert Ni species.•Ni/Al2O3 catalysts present high metal-support interaction, so that only a relative amount of metal is active for CO2 methanation.•Ru/Al2O3 catalysts are more efficient than Ni/Al2O3 in hydrogen dissociation; TOF of the former is about ten times than TOF of Ni catalysts.•Optimal behavior was found for 12% Ni and 4% Ru, which provide metal surfaces of 5.1 and 0.6 m2  g−1, respectively. The hydrogenation of CO2 into CH4 from H2 produced by renewable energy is considered an interesting alternative in order to promote the development of such green energies. In the present work, the effect of Ni and Ru loadings on the catalytic performance of alumina-supported catalysts is studied for CO2 methanation reaction. All catalysts were prepared by wetness incipient impregnation, characterized by several techniques (N2-physisorption, CO2-TPD, XRD, H2-chemisorption, XPS and H2-TPR) and evaluated for CO2 methanation in a fixed bed reactor at GHSV = 10,000 h−1 and W/FCO20 = 4.7 (g cat.) h mol−1. Characterization results showed that addition of increasing loadings of Ni and Ru lead to the formation of both CO2 adsorption and H2 dissociation active sites, which are necessary to carry out CO2 hydrogenation into methane. Easily reducible ruthenium was dispersed on γ-Al2O3 in form of large agglomerates, whereas Ni was better dispersed presenting a great interaction with the support. 12% Ni and 4% Ru resulted to be the optimal contents providing metal surfaces of 5.1 and 0.6 m2 g−1, T50 values of 340 and 310 °C and activity being quite stable for 24 h-on-stream. In terms of turnover frequency (TOF), 4%Ru/Al2O3 catalyst was quite more efficient than 12%Ni/Al2O3, probably due to a greater ability of ruthenium to dissociate hydrogen. The apparent activation energies for alumina supported Ni and Ru were 129 and 84 kJ mol−1, respectively.